The Effect of Contoured Surface, Excavation and Fill Construction to the 3D Settlement Analysis (Himpunan Ahli Teknik Tanah Indonesia, 2023)
Settlement analysis is commonly done by assuming a horizontal soil surface with homogeneous soil layer. This assumption may no longer applicable when construction is conducted on mountainous area where there are a lot of hills or sloping area. Not only due to initial stress is no longer uniform throughout the entire construction area, excavation and fill activities which are required for the land preparation change the stress state of the soil. These problems are aggravated by the fact that soil layer in most of the mountainous area is not horizontal. In this paper, the effect of contoured surface and construction activities such as excavation and fill will be described by using a parking lot building project constructed at the mountainous area. The analysis is carried by using finite element analysis through MIDAS GTS NX. The result will then be compared with the finite element analysis without considering contoured surface and construction activities. The result shows that excavation and fill activities highly affect the settlement profile. For the area where excavation activities are carried, there will be less settlement which is expected due to an increase in over consolidated ratio. On the other hand, fill area experience more settlement due to lower fill modulus an increase in effective stress around the fill area.